Prevalence and risk factors for lifetime suicide ideation, plan and attempt in Chinese men who have sex with men. Issue 1 (December 2016) - Mu, Huijuan; Li, Yanxia; Liu, Li; Na, Jun; Yu, Liya; Bi, Xuejuan; An, Xiaoxia; Gu, Yuan; Zhou, Yan; Li, Shuang; Zhang, Rui; Jiang, Chao; et al.
Abstract Background To describe the level and risk factors for suicidal behaviors in Chinese men who have sex with men (MSM). Methods A total of 807 MSM were recruited using a respondent-driven sampling method from Anshan, Benxi, Dandong, and Shenyang cities in northeastern China. Results Chinese MSM had lifetime prevalences of suicide ideation (18.3 %), plan (8.7 %) and attempt (4.6 %) that were about 2.8, 5.8 and 5.8 times greater than that of male adults in the general population of China. The MSM with any psychiatric disorders were 4–7 times more likely to think about, plan or attempt suicide than those MSM with no disorder, and there was a clear relationship between the number of comorbid disorders and suicidal behaviors. Multiple regression analysis showed that major depression, bipolar disorder, dysthymia and alcohol use disorder significantly increased the risk for suicide ideation, but not for suicide attempt. Drug dependence disorder, panic disorder and generalized anxiety disorder significantly increased the risk for suicide attempt, but not for suicide ideation. More advanced education reduced the risk of suicidal behaviors, sexual orientations revealed to or discovered by family members or friends significantly increased risk of these suicidal behaviors. Conclusions Chinese MSM have significantly increased risk for suicidal behaviors, mental disorders and their comorbidities could be the largest risk factors for the elevated suicidal behaviors in Chinese MSM. Reducing the family and social stigma and rejection of homosexual behavior and early detection and effective treatment of psychiatric disorders and their comorbidities in MSM may help to decrease suicidal behaviors of Chinese MSM.